POTRET PEDAGANG KAKI LIMA DALAM PENDIDIKAN ANAK DI KOTA PALANGKA RAYA - Canna Melykson Sinurat; Halna Paltina Sihombing; Saputra Adiwijaya (Prodi Sosiologi FISIP UPR, 2025)
This study explores the lives of street vendors (PKL) in supporting their children's education in Palangka Raya City, focusing on the experience of Ibu Siti. As part of the informal economic sector, Ibu Siti faces various challenges, particularly economic limitations that hinder her children's access to proper education. Although government programs are available to support education for low-income communities, children from street vendor families often struggle to obtain quality education. This research employs a descriptive qualitative approach, using in-depth interviews as the primary method of data collection. Ibu Siti, a long-time street vendor, was selected as the main informant. The findings reveal that despite financial constraints and limited knowledge about educational programs, Ibu Siti continues to prioritize her children's education through various strategies and personal sacrifices.